Implementasi CRM Berbasis Web Untuk Meningkatkan Kepuasan Pelanggan di Toko Adi Glass - Muhammad Fahrozi; Jhonson Efendi Hutagalung; Ruri Ashari Dalimunthe (Institut Teknologi Garut, 2026)
Advances in information technology in the era of digital transformation are driving businesses to leverage technology to enhance competitiveness and service quality. Adi Glass, a business in the home furnishings sector, still faces challenges in managing customer data and sales transactions, which are currently handled manually, thereby reducing service effectiveness and sales performance. This study aims to design and implement a web-based Customer Relationship Management (CRM) system and evaluate its impact on sales performance and customer satisfaction. The method used is a mixed-methods approach involving interviews, observations, literature review, and questionnaires. The results show that the CRM system is capable of integrating customer and sales data and supports structured promotion management. The evaluation indicates a 30% increase in data management efficiency, a 25% increase in service speed, and a 27% increase in customer satisfaction. The contribution of this research lies in the development of an integrated web-based CRM system with promotional features as a sales improvement strategy for small businesses.